Prophylaxis of Peruvian wart, based on etiological and epidemiological own characters from the disease - Arce, Julián (1922)
Peruvian wart or Carrion's disease, which occurs in two well-defined and independent clinical forms: benign and malignant wart wart, etiologic and epidemiologic features characters as identical to those that are characteristic of tropical diseases caused by parasitic protozoa and transmitted by blood-sucking insects, such as malaria, yellow fever, trypanosomiasis, etc., there can be no doubt that it is also produced by a specific protozoan and trasmmitida for hemófago insect.